Recurrent lacrimal abscess in infant - Mondal, Monojit; Biswas, Biswajit; Laha, Sumanta; Roy, Atanu; Barik, Kanai Lal; Datta, Asok Kumar; Bose, Sayan; Biswas, Tanmoy (Asian Journal of Medical Sciences, 2014)
Acute dacryocystitis at or shortly after birth is uncommon and its main complication, formation of lacrimal sac abscess, is rare. Uniform and standard treatment protocol for this condition has not been established till date. We report on a 2 month old infant with an abscess of the lacrimal sac. He was treated for similar condition on day 6 of his life by incision and drainage; unfortunately, the condition recurs. This time, he was managed with incision and drainage under systemic antibiotic cover; and an early probing of the nasolacrimal duct (NLD) was done on 7th post-operative day. The patient was followed up for a period of one year without any further recurrence and complication. Pathophysiology of the condition and possible treatment options in children have been discussed. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10458 Asian Journal of Medical Sciences Vol.6(2) 2015 121-123